2022
DOI: 10.3390/nano12060936
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Graphene-Family Nanomaterials on Plant Growth: A Review

Abstract: Numerous reports of graphene-family nanomaterials (GFNs) promoting plant growth have opened up a wide range of promising potential applications in agroforestry. However, several toxicity studies have raised growing concerns about the biosafety of GFNs. Although these studies have provided clues about the role of GFNs from different perspectives (such as plant physiology, biochemistry, cytology, and molecular biology), the mechanisms by which GFNs affect plant growth remain poorly understood. In particular, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 90 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…[ 41 ] Graphene and other carbon materials have been extensively investigated for the fabrication of plant sensors due to their organic nature and extreme biocompatibility with plants both in vitro and in vivo. [ 42 ] According to Park et al., graphene oxide could be used to improve the growth of A. thaliana plants as well as watermelons. [ 43 ] This study examined the effect of injecting graphene oxide into watermelons, and it was observed that the length of the watermelon's growth increased.…”
Section: Functional Materials For Soft Bioelectronic Interfacesmentioning
confidence: 99%
“…[ 41 ] Graphene and other carbon materials have been extensively investigated for the fabrication of plant sensors due to their organic nature and extreme biocompatibility with plants both in vitro and in vivo. [ 42 ] According to Park et al., graphene oxide could be used to improve the growth of A. thaliana plants as well as watermelons. [ 43 ] This study examined the effect of injecting graphene oxide into watermelons, and it was observed that the length of the watermelon's growth increased.…”
Section: Functional Materials For Soft Bioelectronic Interfacesmentioning
confidence: 99%
“…Nanomaterials play a key role in enhancing plant nutrition, decreasing pests and diseases, and improving stress tolerance in agriculture. 40,41 Carbon dots (CDs) are a novel member of the carbonaceous nanomaterial family and have gained significant attention in several fields with their wonderful properties like easy synthesis process, photo-luminescence, biocompatible nature, presence of various functional group on the surface, nontoxicity, and water solubility. 42 They have been utilized in many applications, including drug delivery, biosensing, photodegradation, reduction, and antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…18 Such changes due to polar group introduction make GO highly hydrophilic which has been used to load, carry, and release valuable drugs including doxorubicin, quercetin, gefitinib, sumatriptan succinate, and cytarabine, which are used as carriers. 19 Aryl-tetralin-type lignans known as podophyllotoxins (PTOXs) are significant natural toxins found in a variety of plant resins (Figure 1). PTOX along with its structural derivatives is currently gaining more attention, especially in cancer patients' chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The covalent bond medication increases the processability and brings new functions to GO, particularly when the excessive OH functional groups on the ages are acidified to produce carboxyl groups and conversion of these groups into esters by using carboxyl activation reagents such as N , N -dicyclohexylcarbodiimide (DCC) and so forth . Such changes due to polar group introduction make GO highly hydrophilic which has been used to load, carry, and release valuable drugs including doxorubicin, quercetin, gefitinib, sumatriptan succinate, and cytarabine, which are used as carriers …”
Section: Introductionmentioning
confidence: 99%